Cervical spine characteristics differ in competitive combat athletes compared with active control participants. (October 2022) - Brown, Daniel A.; Leung, Felix T.; Evans, Kerrie; Grant, Gary; Hides, Julie A.
Abstract: Background: Injury to the head and neck are common in combat sport athletes. Impairments of the cervical spine have been found in some athletes who participate in sports with high forces and collisions. There is a lack of research on the effects of combat sports on the cervical spine. Objective: The primary study aim was to investigate differences in cervical spine characteristics between combat athletes and a similarly aged active control group. The secondary aim was to investigate the relationship between symptom-based outcome measures and characteristics of the cervical spine. Design: Cross-sectional. Method: 40 male adult combat sport athletes and 40 male adult control participants were recruited from 4 combat sport clubs and a university campus, Australia. Cervical spine assessments were conducted at a private physiotherapy clinic. The Neck Disability Index and the Post-Concussion Symptom Scale were used as symptom-based outcome measures. Results: Combat sport athletes had a reduced range of cervical motion, but greater isometric strength and endurance compared with a control group ( p  < 0.05). The Neck Disability Index and Post-Concussion Symptom Scale were negatively correlated with cervical spine range of motion and isometric strength, meaning that higher scores correlated with a reduction in function. Conclusions: Differences were observed in characteristics of the cervical spine in combat sport athletes compared with a control group. Higher symptom-based outcome scores correlated with reduced range of motion and strength of cervical spine muscles. Further investigation to establish clinical cut-off scores for functional impairment may be warranted. Highlights: Combat sport athletes have reduced range of motion of the cervical spine. Cervical spine muscle isometric strength and endurance is greater in combat sport athletes. Cervical spine range of motion and strength is negatively related to disability and symptom presentation.